PHENOMENA AND BIFURCATION ANALYSIS OF AN AEROELASTIC SYSTEM WITH IMPACT EFFECTS - Vasconcellos, Rui M. G. [UNESP]; Abdelkefi, Abdessattar; ASME (Amer Soc Mechanical Engineers, 2014)
Impacts can happen in real aircraft movable surfaces, such as ailerons, flaps, rudder, elevators, trim tabs among others secondary control surfaces leading to complex, dangerous and unpredictable transitions. In a real mechanism, impacts can occur when the surface displacement increases and then regions of higher stiffness or impacts can take place. Abrupt transitions from LCO to chaos and secondary complex transitions are directly related with the discontinuous nature of impact systems, these abrupt transitions caused by impacts are different from the well-known routes to chaos. In this work, numerical simulations generate the data basis for the analysis of a two degrees of freedom aeroelastic wing with a nonlinearity in the pitch stiffness simulating an impact at higher angles. The objective is to characterize the behavior of this system with parametric variation and understand the mechanisms related to the observed bifurcations.